Microbleed clustering in thalamus sign in CADASIL patients with NOTCH3 R75P mutation - Takei, Jun; Higuchi, Yujiro; Ando, Masahiro; Yoshimura, Akiko; Yuan, Jun-Hui; Fujisaki, Natsumi; Tokashiki, Takashi; Kanzato, Naomi; Jonosono, Manabu; Sueyoshi, Takeshi; Kanda, Naoaki; Matsuoka, Hideki; et al. (Frontiers in Neurology, 2023)
Background and Objective: Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarct and Leukoencephalopathy (CADASIL) is an inherited cerebral microvascular disease characterized by the development of vascular dementia and lacunar infarctions. Aim of this study is to identify the genetic and clinical features of CADASIL in Japan.We conducted genetic analysis on a case series of patients clinically diagnosed with CADASIL. Clinical and imaging analysis were performed on 32 patients with pathogenic mutations in the NOTCH3 gene. To assess the presence of cerebral microbleeds (CMBs), we utilized several established rating scales including the Fazekas scale, Scheltens rating scale, and Microbleed Anatomical Rating Scale, based on brain MRI images.Results: Among the 32 CADASIL patients, 24 cases were found carrying the R75P mutation in NOTCH3, whereas the remaining eight cases had other NOTCH3 mutations (R75Q, R110C, C134F, C144F, R169C, and R607C). Haplotype analysis of the R75P mutation uncovered the presence of a founder effect. Brain MRI analysis revealed that cases with the R75P mutation had a significantly higher total number of CMBs, particularly in the thalamus, when compared to patients with other NOTCH3 mutations.Among 15/24 of cases carrying the R75P mutation, we observed a notable clustering of CMBs in the thalamus, termed as the Microbleeds Clustering in Thalamus sign (MCT sign).We propose that the MCT sign observed in NOTCH3 R75P-related CADASIL patients may serve as a potentially characteristic imaging feature. This finding offers further insights into the interactions between genotypes and phenotypes between NOTCH3 and CADASIL.